IS FRAGMENTED QRS ASSOCIATED WİTH THE SEVERITY OF CAROTID ARTERY DISEASE? - Efe Edem; Hasan Reyhanoğlu (Sakarya Tıp Dergisi, 2018)
Objective: This study investigated the association between fragmented QRS and the severity of carotid artery disease.Materials and Methods: 168 patients who underwent carotid angiography due to transient ischemic attack or ischemic stroke between March 2009 and July 2017 were enrolled in the study. Patients enrolled in the study were divided into two groups according to severity of carotid artery disease on carotid angiography. Group One consisted of patients with a carotid stenosis of lt;50% (n:82) and group 2 consisted of patients with a carotid stenosis of ≥50% (n:86). Two groups were compared in terms of existence of fragmented QRS on electrocardiogram prior to carotid endarterectomy by using hospital records.Results: The study group consisted of 168 patients. Group One showed more male predominance and this indicated a significant difference in terms of gender between two groups (p=0.026). Existence of chronic obstructive pulmonary disease was more common in group 2 and this indicated a statistically significant difference (p=0.001). 12-lead ECG of patients in group 2 tended to demonstrate fQRS much frequently compared to patients in group 1 (p=0.002).